Altered Long Noncoding RNA and Messenger RNA Expression in Experimental Intracerebral Hemorrhage - a Preliminary Study - Cui Hanjin; Liu Tao; Li Pengfei; Yang Ali; Zhou Huajun; Luo Jiekun; Wang Yang; Tang Tao (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Functional recovery in the chronic phase is a difficult problem in intracerebral hemorrhage (ICH) treatment. Long noncoding RNAs (lncRNAs) are demonstrated to be involved in central nervous system (CNS) disorders. However, the roles of lncRNAs in post-ICH injury and repair are poorly understood, especially those that may be attributed to long-term neurological deficit. The present study depicted the lncRNA and messenger RNA (mRNA) profile by microarray at late stage after an experimental ICH. Methods: LncRNA and mRNA microarray was used to first identify differentially expressed genes. Gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to determine bio-functions and signaling pathways, with which differentially expressed genes are most closely related. Quantitative real-time polymerase chain reaction (PCR) was used to validate the results of microarray. Finally, the lncRNA-mRNA co-expression network was constructed to find the interaction of genes. Results: A total of 625 differentially expressed lncRNAs and 826 expressed mRNAs were identified. Altered genes were enriched in mitochon-drial matrix, G-protein coupled receptor signaling pathway, and olfactory transduction, which may be associated with ICH-induced pathophysiologic changes in the long term. A co-expression network profile based on 5 validated differentially expressed lncRNAs and 205 interacted mRNAs was composed of 210 nodes and 298 connections. Conclusion: Mitochondrial matrix, reduced G-protein coupled receptor activity, and impaired olfactory transduction may be involved in the sequelae following ICH. Further, these dysregulated lncRNAs and mRNAs may be the promising therapeutic targets to overcome obstacles in functional recovery following ICH.